2019
DOI: 10.48550/arxiv.1912.10296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-metric construction of spacetime defects

Abstract: We describe a spacetime endowed with a non-metricity tensor which effectively serves as a model of a spacetime foam. We explore the consequences of the non-metricity in several f (R) theories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Some of these works put forward that gravity theories with non-metricity can avoid the spacetime singularities present in GR already at a classical level [81,82]. It has also been suggested that non-Riemannian geometries could be successful in being a low-energy effective description of theories of quantum gravity, as they could be more suited in accounting for features of a quantum-spacetime that may exist at high energies [63,[83][84][85][86]. Hence, that the existence of non-metricity should be experimentally probed at different energy scales.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these works put forward that gravity theories with non-metricity can avoid the spacetime singularities present in GR already at a classical level [81,82]. It has also been suggested that non-Riemannian geometries could be successful in being a low-energy effective description of theories of quantum gravity, as they could be more suited in accounting for features of a quantum-spacetime that may exist at high energies [63,[83][84][85][86]. Hence, that the existence of non-metricity should be experimentally probed at different energy scales.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these works put forward that gravity theories with non-metricity can avoid the spacetime singularities present in GR already at a classical level [70,71]. It has also been suggested that non-Riemannian geometries could be successful in being a low-energy effective description of theories of quantum gravity, as they could be more suited in accounting for features of a quantum-spacetime that may exist at high energies [61,[72][73][74][75]. This makes clear that the existence of non-metricity should be experimentally tested at different energy scales.…”
Section: Introductionmentioning
confidence: 99%